2017
DOI: 10.18388/abp.2016_1339
|View full text |Cite
|
Sign up to set email alerts
|

How short RNAs impact the human ribonuclease Dicer activity: putative regulatory feedback-loops and other RNA-mediated mechanisms controlling microRNA processing

Abstract: Ribonuclease Dicer plays a pivotal role in RNA interference pathways by processing long double-stranded RNAs and single-stranded hairpin RNA precursors into small interfering RNAs (siRNAs) and microRNAs (miRNAs), respectively. While details of Dicer regulation by a variety of proteins are being elucidated, less is known about non-protein factors, e.g. RNA molecules, that may influence this enzyme's activity. Therefore, we decided to investigate the question of whether the RNA molecules can function not only as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 60 publications
(96 reference statements)
2
9
0
2
Order By: Relevance
“…Under these conditions, accumulation of GlmZ* may limit further processing of full-length GlmZ thereby maintaining a robust GlmS basal level. Interestingly, a similar regulatory scenario has also been proposed for human microRNAs [36]. In this case, miRNAs such as miR-21-5p were shown to inhibit their own biogenesis from the corresponding miRNA precursors, at least in vitro.…”
Section: Expression Of the Srna Chimeras Mimicking Glmz* Augments Glmmentioning
confidence: 53%
“…Under these conditions, accumulation of GlmZ* may limit further processing of full-length GlmZ thereby maintaining a robust GlmS basal level. Interestingly, a similar regulatory scenario has also been proposed for human microRNAs [36]. In this case, miRNAs such as miR-21-5p were shown to inhibit their own biogenesis from the corresponding miRNA precursors, at least in vitro.…”
Section: Expression Of the Srna Chimeras Mimicking Glmz* Augments Glmmentioning
confidence: 53%
“…Previously we have shown that hDicer, apart from the canonical substrates, binds structurally diverse short ssRNA molecules [35][36][37][38]. Consequently, we decided to test whether hDcr and its variants lacking the PAZ domain would cleave short ssRNAs.…”
Section: Rnase Activity Of Full-length Hdicer and The Paz Domain Delementioning
confidence: 99%
“…Wpływają one na zmiany struktury Dicer, uczestniczą w sekwestracji białka lub jego translokacji w obrębie komórki. W ostatnim czasie pojawiają się również doniesienia wskazujące na to, że nie tylko czynniki białkowe, ale również cząsteczki kwasów nukleinowych są zaangażowane w regulację aktywności Dicer [60,72,73]. W komórkach ludzkich oraz C. elegans w obrębie cząsteczek mRNA i lncRNA zidentyfikowano tzw.…”
Section: Rola Dicer W Biogenezie Mirnaunclassified